Prolonged Intractable Hiccups Associated with HSV (I&II) Esophagitis and H. pylori Gastritis - Hopkins, Christina; Bansari, Asha; Ladna, Michael; Dideban, Bahram (Case Reports in Infectious Diseases, 2023)
An immunocompetent male presented with an intractable hiccup. EGD revealed circumferential ulceration of middistal esophagus and biopsies confirmed HSV (I&II) esophagitis and H. pylori gastritis. He was prescribed triple therapy for H. pylori and acyclovir for HSV esophagitis. HSV esophagitis and H. pylori should be included in differential for intractable hiccups.